Diagnostic techniques for bacterial diseases in shrimp farming - Varela, Alexander (2020)
Farmed shrimp are constantly threatened by infectious diseases. The increasing pressure on production demands high performance and efficiency that can only be achieved by eliminating or reducing the impact of pathogens. The timely detection of diseases is of great importance, so it is required to have a clear command of the advantages and disadvantages of different diagnostic techniques, in order to implement a rapid response to outbreaks that may occur. Obtaining a diagnosis will depend on various factors, including the early detection of clinical signs and the correct interpretation of the results. In this way, the selection of techniques that allow a preliminary approach to a health emergency and the confirmatory tests that will lead to the design of actions to be chosen. The aim of this paper was to present the advantages and disadvantages of the diagnostic techniques currently available for the identification of bacterial agents that affect shrimp, providing information for objective decision-making that allows solving sanitary problems in aquaculture production.